Controlling Performance of Organic–Inorganic Hybrid Perovskite Triboelectric Nanogenerators via Chemical Composition Modulation and Electric Field‐Induced Ion Migration. Issue 47 (9th November 2020) - Huang, Shuyi; Shi, Lin; Zou, Taoyu; Kuang, Haoze; Rajagopalan, Pandey; Xu, Hongsheng; Zhan, Shijie; Chen, Jinkai; Xuan, Weipeng; Jin, Hao; Dong, Shurong; Zhou, Hang; et al.
Abstract: In this paper, new strategies are proposed to design high‐performance organic–inorganic hybrid perovskite (PVK)‐based triboelectric nanogenerators (TENGs) via both chemical composition modulation and electric field‐induced ion migration in the films. Both composition variation and ion migration under electric field are found to change the type of conductivity of the perovskite films, then modify their surface potentials and electron affinities. These are utilized to fabricate PVK‐based TENGs in pairs with poly‐tetrafluoroethylene (PTFE) or nylon films, respectively. Results show that PVK films are able to work as either a positive or a negative tribo‐material depending on the tribo‐material pair used; the optimal performances are obtained for PTFE/PVK TENGs using a PVK film with a MAI/PbI2 ratio of 2 and forward polarization, and for nylon/PVK TENGs using a PVK film with a MAI/PbI2 ratio of 0.4 and reverse polarization, respectively. The maximum output voltage and peak power density of PTFE/PVK TENGs are about 979 V and 24 W m −2, 2.5 and 6.5 times higher than those of TENGs with nonoptimal composition ratio or that are poorly polarized. This work provides a new material design method for high‐performance TENGs and a novel polarization strategy for TENG performance enhancement. Abstract : The chemical composition modulation and electric field‐induced ion migration of organic‐inorganic hybrid perovskites are utilized to fabricate performance‐enhanced triboelectric nanogenerators (TENGs). The chemical composition modulation induced conductive type conversion and electric field‐induced self‐doping on the surfaces enable controlled performance of the TENGs.